Boredom and meaningful activity in adults experiencing homelessness: A mixed-methods study. (December 2019) - Marshall, Carrie Anne; Davidson, Lisa; Li, Andrea; Gewurtz, Rebecca; Roy, Laurence; Barbic, Skye; Kirsh, Bonnie; Lysaght, Rosemary
Background: Boredom has been reported as a frequent problem experienced by homeless persons, with implications for mental and social well-being. Purpose: This study aimed to explore the nature and impact of boredom in the lives of homeless and formerly homeless persons. Method: A mixed-methods design was used to engage 13 participants in a structured 92-item quantitative interview using six standardized measures, followed by a semistructured qualitative interview. Correlational analyses were performed with the data compiled from the quantitative interviews, and grounded theory strategies were used to analyze our qualitative data. The two analyses were integrated at the stage of interpretation. Findings: Boredom was described as a profound and pervasive experience for homeless persons, imposing deleterious impacts on mental well-being and driving substance use. A strong positive correlation between meaningful activity and mental well-being ( r s = .767, p <. 01) and a strong negative correlation between boredom and belonging in one's community ( r s = –.771, p < .01) were identified. Implications: Boredom is a critical topic of study for occupational therapy in the area of homelessness. Future research is needed to design and test interventions to optimize the mental well-being, participation, and social connectedness of this population.